GAMIFIED LISTENING PRACTICE THROUGH AI APPS: MOTIVATION AND LEARNING OUTCOMES IN UZBEK 7TH GRADERS (Лучшие интеллектуальные исследования, 2025)
Abstract: The growing presence of Artificial Intelligence (AI) and gamification in language learning has introduced innovative methods for developing listening skills among young learners. This study investigates the impact of gamified AI-based listening applications on the motivation and listening proficiency of 7th grade students in Uzbekistan. Drawing on classroom observations, student surveys, and teacher interviews, the research explores how elements such as points, badges, challenges, and adaptive feedback influence learners’ engagement and academic outcomes. The findings indicate that gamified listening tools significantly increase intrinsic motivation, promote frequent listening practice, and enhance comprehension by offering personalized and interactive learning experiences. Students using such apps consistently demonstrate better recognition of spoken English, improved vocabulary acquisition, and increased confidence in classroom communication. However, the study also identifies challenges related to digital access, cultural relevance of content, and integration with the national curriculum. The research concludes by recommending the localization of gamified AI tools and targeted teacher training to optimize their impact on language education in the Uzbek context.